Analisis terhadap Timbulnya Hak Servituut Ditinjau dari Proses Pemecahan Bidang Tanah yang Salah - Muhammad Husein Abdullah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study provides an in-depth examination of the emergence of servitude rights (hak servituut) arising from procedural errors in land parcel division, which result in landlocked plots without road access. Servitude rights, as regulated in Article 674 of the Indonesian Civil Code and reinforced by the Conversion Provision of Article I point 6 of the Basic Agrarian Law (UUPA), constitute a legal burden imposed on one parcel of land for the benefit of another, thereby ensuring that landlocked owners gain reasonable access. Although the UUPA serves as the national agrarian framework, the servitude concept remains highly relevant and functions as a crucial legal instrument to safeguard the rights of affected landowners. This research employs a normative juridical approach, integrating statutory and conceptual analyses to explore the consistency between legal theory and practice. The findings demonstrate that parcel division conducted without considering the social function of land, as mandated by Article 6 of the UUPA, can trigger access disputes that adversely affect community interests. Dispute resolution may proceed through litigation or non-litigation channels, with mediation emerging as the more effective and efficient option for maintaining harmonious relations between parties. Article 667 of the Civil Code provides a clear legal basis for landlocked property owners to obtain access while obligating them to pay fair compensation to the burdened land. Based on these findings, the study recommends strict adherence to lawful land division procedures and the development of detailed technical guidelines on servitude compensation to prevent future disputes and to strengthen legal certainty for all stakeholders.